PEMBELAJARAN PAI INTERAKTIF BERBASIS DIGITAL: TRANSFORMASI METODE KLASIK UNTUK MENINGKATKAN KETERLIBATAN SISWA SMK BIFAHMIDDIN KAPUAS - Wahidin; aulia aulia; Ahmad Habibi; Ahmad Khoirudin; Purnama Sari (IAI DARUL ULUM KANDANGAN, 2025)
This article aims to examine the relevance of lecture and question and-answer methods in Islamic Religious Education (PAI) learning in the Generation Z era, particularly at SMKS Bihfahmiddin. Using a descriptive qualitative approach, this research involved PAI teachers and 11th-grade students as subjects. Data were collected through interviews, observations, and documentation. The findings indicate that the lecture method, when combined with question-and-answer techniques and digital media, positively impacts students' comprehension. Generation Z students demonstrated enthusiasm and active participation when engaged in interactive learning. The transformation from classical to interactive teaching methods proves to be relevant and effective in enhancing PAI learning in the digital age.